PENINGKATAN SOSIAL EMOSIONAL ANAK MELALUI PERMAINAN OUTDOOR PADA KELOMPOK A DI Taman Kanak-kanak - Chandra Nur Fitria; Komala Komala (IKIP Siliwangi, 2019)
Child social emotional development at this time requires the attention of all parties, especially teachers in the school because it is not optimal child social-emotional development because teacher learning activities do not provide stimulation to children. In addition, emotional tension possessed by children can reduce or interfere with the motor and mental activities of children. One way to develop children's social emotional and physical can be done through out door games. This research method is classroom action research with the aim of providing information on how the teacher acts in stimulating children's social emotional development through out door games. Based on the results of the study, the results of the initial conditions of development of the social-emotional abilities of group A children are still low, so it needs to be developed. After the implementation of the action through two cycles with three meetings per cycle shows the results of improvement. The results of the research conducted by researchers showed that learning activities through outdoor play activities applied to children showed an increase in the number of early childhood children who were able to master learning about the form of the game. The results of the research conducted by researchers showed that learning activities through outdoor play activities applied to children showed an increase in the number of early childhood children who were able to master learning about the form of the game. Based on the results of this study, children can grow mutual help, get new playmates, train their children to take turns playing, grow joy while playing, and children become brave to play alone without having to be accompanied. So it can be concluded that there is an increase in children's social emotional through out door games.Perkembangan sosial emosional anak pada saat ini memerlukan perhatian dari semua pihak terutama guru di sekolah sebab belum optimalnya perkembangan sosial-emosional anak karena kegiatan pembelajaran guru kurang memberikan stimulasi pada anak. Selain itu ketegangan emosi yang dimiliki anak bisa mengurangi atau mengganggu kesibukan motorik dan jiwa anak. Salah satu cara pengembangan sosial emosional dan fisik anak dapat dilakukan melalui permainan out door. Metode penelitian ini yaitu penelitian tindakan kelas dengan tujuan memberikan informasi bagaimana tindakan guru dalam menstimulasi perkembangan sosial emosional anak melalui permainan out door. Berdasarkan hasil penelitian menunjukkan hasil kondisi awal perkembangan kemampuan sosial-emosional anak kelompok A masih rendah, sehingga perlu dikembangkan. Setelah pelaksanaan tindakan melalui dua siklus dengan tiga pertemuan per siklus menunjukan hasil peningkatan. Hasil penelitian yang dilakukan peneliti menunjukan bahwa kegiatan pembelajaran melalui kegiatan permainan outdoor yang diterapkan pada anak menunjukkan peningkatan jumlah anak usia dini yang mampu menguasai pembelajaran mengenal bentuk permainan. Berdasarkan hasil penelitian ini anak-anak dapat menumbuhkan rasa saling tolong menolong, mendapatkan teman bermain yang baru, melatih kesabaran anak agar mau bergiliran dalam bermain, menumbuhkan keceriaan saat bermain, serta anak menjadi berani bermain sendiri tanpa harus ditemani. Sehingga dapat disimpulkan bahwa adanya peningkatan sosial emosional anak melalui permainan out door.